Surface Cooling of a Pool Fire by Aqueous Foams. Issue 5 (4th May 2017) - Conroy, Michael W.; Fleming, James W.; Ananth, Ramagopal
ABSTRACT: We model an idealized case of heat transfer relevant for foams used to suppress pool fires wherein an ambient-temperature firefighting foam is placed uniformly and instantaneously on top of a hot fuel pool with a boiling point slightly lower than that of water. We performed experiments using n -heptane fuel and both commercial fluorinated (AFFF) and non-fluorinated (RF6) foams. The measurements show rapid (<10 s) and significant (25°C) cooling of the fuel close to the foam-fuel interface in good agreement with the model predictions. The model also shows that a 60-µm-thick static, aqueous film formed between the foam and fuel surface has a negligible effect on interfacial cooling. Therefore, in addition to forming a fuel-transport barrier to the fire, the foam layer rapidly cools the surface by heat conduction and suppresses fuel evaporation, which suppresses the pool fire.